2019
DOI: 10.1002/jgc4.1161
|View full text |Cite
|
Sign up to set email alerts
|

Yield of whole exome sequencing in undiagnosed patients facing insurance coverage barriers to genetic testing

Abstract: Background Despite growing evidence of diagnostic yield and clinical utility of whole exome sequencing (WES) in patients with undiagnosed diseases, there remain significant cost and reimbursement barriers limiting access to such testing. The diagnostic yield and resulting clinical actions of WES for patients who previously faced insurance coverage barriers have not yet been explored. Methods We performed a retrospective descriptive analysis of clinical WES outcomes for patients facing insurance coverage barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 36 publications
5
40
0
Order By: Relevance
“…The lack of knowledge parents perceived by insurance representatives led to greater frustrations when payors did not consider the medical bene ts and long-term cost savings of access to equipment, therapy, and diagnostics. This is consistent with studies that have indicated barriers to diagnosis and diagnostic testing for rare diseases (7,45). Parents in this study expressed frustration that insurance…”
Section: Discussionsupporting
confidence: 91%
“…The lack of knowledge parents perceived by insurance representatives led to greater frustrations when payors did not consider the medical bene ts and long-term cost savings of access to equipment, therapy, and diagnostics. This is consistent with studies that have indicated barriers to diagnosis and diagnostic testing for rare diseases (7,45). Parents in this study expressed frustration that insurance…”
Section: Discussionsupporting
confidence: 91%
“…Notably, the UDN has a mandate to accept individuals without regard to their insurance or financial status; therefore geographic and financial barriers are minimized beyond what can be achieved in clinical practice, to improve equity in access to those with the most diagnostically intractable diseases. As a result, individuals who have no access to clinical ES or are denied ES coverage by insurance continue to be accepted by the network, 38 leading to some diagnoses that could be tractable in a clinical setting. This number is declining as clinical reimbursement for ES increases, although unlikely to ever become zero.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical whole-exome sequencing (WES) has a reported diagnostic rate of 25%-30% (Yang et al 2013;Lazaridis et al 2016;Retterer et al 2016;Reuter et al 2019). Here we used research-based WES followed by clinical confirmation of the variants to diagnose a proband presenting with a history of multiple melanomas.…”
Section: Discussionmentioning
confidence: 99%